Gli studi gramsciani nel mondo germanofono: un bilancio attuale - Pohn-Lauggas, Ingo (International Gramsci Journal, 2023)
This is the Abstract of the Italian-language article by Ingo Pohn-Lauggas on the current position of Gramsci in the Germanophone (Austria and Germany) area.